Floristics In Rustic Style as An Example of Practical Eco-Design in The Modern World Rustic Style Floristics as An Example of Practical Eco-Design in The Modern World - Vladyslava Nahorna (Emerging Frontiers Library for The American Journal of Interdisciplinary Innovations and Research, 2025)
The purpose of this article is to define methodological approaches and the practical application of the rustic style as an example of practical eco-design in the modern world. The research methods used in the article include: abstract- logical method; system analysis; observation and generalization; analysis and synthesis; expert evaluation methods; and graphical method. This study identifies the fundamental concepts and structure of the rustic style. It examines how, in floristic art, the rustic decoration direction is expressed in compositions that use wildflowers (according to season), dried flowers and cereal grasses, tree branches, moss, bark, fabrics of natural fibers such as burlap, linen, ropes, and wooden elements. Key ecological principles embodied in the rustic style are defined, including the use of local resources; recycling and reuse; simplicity and conscious consumption. The main principles and characteristics of decorating with natural materials are determined—use of seasonal and locally grown plants; emphasis on recycling and reusing items (e.g., glass jars, wooden boxes, bottles); rejection of synthetic plastic, floral foam, and glitter; décor that influences emotions by calming, inspiring, and shaping style. Furthermore, the study finds that one of the key features of rustic interiors is the widespread use of untreated wood, which must not be painted or varnished but only treated with special agents for pest protection. The use of rustic style in decorating modern offices, cafés, and other spaces is characterized, and its negative aspects and limitations are identified: risk of appearing careless or overly simplistic; stylistic constraints; seasonal dependence; durability issues; difficulties in cleaning and transporting décor; limited color palette; and lack of technological compatibility.